PENGARUH GAYA KEPEPIMPINAN TERHADAP PRODUKTIVITAS PEGAWAI DI KANTOR KELURAHAN BORONG KOTA MAKASSAR - M. Mubdi Fahril; Zalkha Soraya; Alamsjah (STKIP Subang, 2026)
This study aims to examine the effect of leadership style on employee productivity in the public service sector, particularly at the village administrative level. The urgency of this research is grounded in the increasing complexity of public service demands, which require higher effectiveness and efficiency in employee performance. This study employs a quantitative approach with an associative research design, involving 30 respondents selected through a saturated sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and simple linear regression analysis. The results indicate that leadership style has a positive and significant effect on employee productivity, with a t-value of 4.209 exceeding the t-table value of 2.048 and a significance level of 0.000 (p < 0.05). These findings suggest that more effective leadership styles contribute directly to increased employee productivity. Theoretically, this study reinforces the transformational leadership framework in the context of public organizations. Practically, it provides strategic implications for improving human resource management at the village level to enhance the quality of public service delivery.